On a class of Chinese hyperrings - Jančić Rašović, Sanja (Italian Journal of Pure and Applied Mathematics, 2011)
In this paper we have shown one construction of the Chinese hyperrings, using the class of multiendomorphisms of the starting ring (R,+.) or the class of multiendomorphisms of its additive group (R,+).